Impelementasi Strategi Pembelajaran berbasis Inklusif: Studi Kasus Anak dengan Latar Belakang Autisme - Retno Lestari, Anindra; Nazarullail, Fikri (Program Studi Pendidikan Guru Pendidikan Anak Usia Dini, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Trunojoyo Madura, 2024)
Article reviews the inclusion approach in implementing learning strategies for children with autism. This article aims to provide an overview of the implementation of learning strategies provided and carried out for children with special needs, namely autism, at the Raudhatul Athfal (RA) educational institution. This is a form of effort that education is a right for all groups. This research is a qualitative case study type research which aims to describe the results of researchers' findings on problems found in the field. The subjects of this research are special needs children with autism disorders. Data collection techniques in this research used observation and interviews. Data analysis was carried out using the Miles & Huberman interactive analysis model, namely data reduction, data display and drawing conclusions. The results show that the absence of inclusion classes at RA Bakti Telang is not an obstacle in providing educational services. The inclusion approach, strategies and methods provided are the same as for normal children at RA Bakti Telang. Cooperative, affective strategies, storytelling methods, storytelling, works of art, field trips are still taught to children with autism at RA Bakti Telang with the institution's openness to accepting children with special needs. Children will be able to adapt to the environment with encouragement, teaching and innovation in the learning provided. This research contributes to providing a strategy for implementing learning in children with autism disorders